IDENTIFIKASI JENIS-JENIS ROTAN PADA KAWASAN ARBORETUM UNIVERSITAS RIAU - Teddy Noor Hidayat; Defri Yoza; Evi Sri Budiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Rattan is one of timber forest products that was commercial and high value. Arboretum area was located in University of Riau, has a collection of rattan. However, the data information on the types of rattan was contained in the arboretum area does not exist, it is necessary to do this research. The purpose of this research is to determine the types of rattan found in the Arboretum Area in University of Riau and was knowing rattan species diversity found in the arboretum Area in University of Riau. This research have been used descriptive data analysis or describe data obtained directly in the field. The results has been  showed that the types of rattan that are in arboretum Area in University of Riau is Rattanudang (KorthalsiaechinometraBeccari), Rattan umbut (DaemonoropskorthalsiiBlume), Rattan manau(CalamusmananMiquel), Rattan manautikus (Calamustumidus Furtado), Rattan bubuai(Plectocomiaelongata Martius ex Blume) and Rattan rukong(Daemonoropssabut Becc). The results was showing the value of diversity index rattan species in the arboretum area University of Riau is low with the value H '1.57.Keywords:Rattan, Identification,Calamus,Daemonorops,Korthalsia,Plectocomia